MENINGKATKAN HASIL BELAJAR IPS DENGAN MENGGUNAKAN METODE INQUIRI SISWA KELAS IVA SDN 006 KUBANG JAYA KECAMATAN SIAK HULU - Rasyad, Rosani (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2017)
The low learning outcome of IPS students is the background of this research. This is seen from 35 students only 6 students who achieve the minimum mastery criteria of 70.00. The average of IPS learning result obtained by students is 56,15 with enough category. Based on this is the researcher doing research by applying the method of inquiri. This study is a classroom action research, conducted in two cycles, each cycle consisting of two meetings and one daily adventure. The result of research indicated that after applied inquiri method of learning result of IPS student have improvement, this can be seen: (a) in cycle I the total number of complete student is 23 students (65,71%) meanwhile student learning result average is 72,30 (Good); and (b) in cycle II the number of completed students has increased with the number of students 31 students (88.57%) with the average learning outcomes obtained is 82.30 (Very Good).